2011
DOI: 10.1136/emermed-2011-200493
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of therapeutic hypothermia in unconscious patients after near-hanging

Abstract: In this study, outcomes in unconscious near-hanging patients with cardiac arrest were poor despite treatment with TH. Before recommending TH in near-hanging patients, a prospective, randomised controlled study is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…A potential cause for the relatively high percentage of patients with a good outcome (15%) could have been the neuro-protective effects of cold water, with patients presenting with core temperature of circa 34 • C. 16 Our study showed a higher survival rate and a better neurologic outcome compared with previous data which included hanging as a cause of asphyxial cardiac arrest. 15,20 We suggest that aside for airway insufficiency, vascular or neural problems contribute to cardiac arrest after hanging-related injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential cause for the relatively high percentage of patients with a good outcome (15%) could have been the neuro-protective effects of cold water, with patients presenting with core temperature of circa 34 • C. 16 Our study showed a higher survival rate and a better neurologic outcome compared with previous data which included hanging as a cause of asphyxial cardiac arrest. 15,20 We suggest that aside for airway insufficiency, vascular or neural problems contribute to cardiac arrest after hanging-related injury.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these constraints, 111 patients were examined to study the effects of TH on asphyxial cardiac arrest, which is a considerably larger number of subjects than in previous studies. 9,10,[15][16][17]20 It is also important to note that hypoxia was examined in this research solely when drowning and hanging were not considered as criteria for the cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment might also be beneficial after non-shockable or in-hospital cardiac arrest9 10; however, the literature related to the application of therapeutic hypothermia, specifically for comatose survivors of airway obstruction, including near-hanging,11 submersion12 and advanced laryngeal cancer, is limited 13. Lee et al 14 concluded that outcomes in unconscious near-hanging patients with CPA were poor despite treatment with therapeutic hypothermia because of the more severe nature of ischaemic brain injury after cardiac arrest owing to asphyxia than from ventricular fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…There are small case series and case reports describing variable neurological outcomes when TTM was used after cardiac arrest associated with various etiologies [25][26][27][28][29][30][31][32][33][34][35][36][37][38] . A case series of 14 consecutive comatose survivors of asphyxia that were treated with TTM observed a survival rate of 65% 25 .…”
Section: Quality Of Evidence: Low Strength Of Recommendation: Conditimentioning
confidence: 99%
“…A case series of 14 consecutive comatose survivors of asphyxia that were treated with TTM observed a survival rate of 65% 25 . In another retrospective cohort study of 16 unconscious patients after near hanging, 13 patients received TTM and 12 of them had poor neurological outcomes 38 .…”
Section: Quality Of Evidence: Low Strength Of Recommendation: Conditimentioning
confidence: 99%